PENGARUH JENIS KEMASAN PENYIMPANAN TERHADAP VIABILITAS DAN VIGOR BENIH KORO PEDANG PUTIH (Canavalia ensivormis) - Maria Familia Fernandez; Yekti Maryani; Darnawi Darnawi (JURNAL ILMIAH AGROUST, 2018)
This research aims to know about the effect of storage packaging on the viability and vigor of white jack bean. This research was conducted at the Laboratory of the Faculty of Agriculture, Sarjanawiyata Tamansiswa University, Jalan Batikan 02, Yogyakarta.Average temperature of storage space 26-300C and humidity 78%.It was conducted from June to September 2017. The experiment was conducted using one factorial experiment arranged in Completely Randomized Design (RAL). Treatment consists of one factor, namely storage packaging.The acidity used is paper packaging, plastic packaging, and canned packaging.While the controls use seeds of jack bean that are still in pods. Each treatment was repeated five times with sampling of 200 seeds of white sword on each storage container. Observations made include increased moisture content, viability, and seed vigor after storage. The result of the analysis showed that there was no real effect of storage packaging treatment on viability, but had a significant effect on vigor of white sword seedThis research aims to know about the effect of storage packaging on the viability and vigor of white jack bean. This research was conducted at the Laboratory of the Faculty of Agriculture, Sarjanawiyata Tamansiswa University, Jalan Batikan 02, Yogyakarta.Average temperature of storage space 26-300C and humidity 78%.It was conducted from June to September 2017. The experiment was conducted using one factorial experiment arranged in Completely Randomized Design (RAL). Treatment consists of one factor, namely storage packaging.The acidity used is paper packaging, plastic packaging, and canned packaging.While the controls use seeds of jack bean that are still in pods. Each treatment was repeated five times with sampling of 200 seeds of white sword on each storage container. Observations made include increased moisture content, viability, and seed vigor after storage. The result of the analysis showed that there was no real effect of storage packaging treatment on viability, but had a significant effect on vigor of white sword seed.